Implementasi Metode Group Algorithm Programming Sebagai Sistem Pendukung Keputusan Dalam Pemilihan Berita Pada Media Online - Taufik Akbar Maulana; Zulham Sitorus (Bulletin of Information Technology (BIT), 2024)
− News is current information selected by journalists for publication in digital electronic media. News also refers to reports of events deemed to attract the attention of the mass media public. In the process of selecting the main news, the news must meet specific criteria determined by the coverage coordinator. These criteria help to determine which news will be chosen as the main news. Information related to news criteria can be stored in a database, making the evaluation and selection process easier compared to using hardcopy. Additionally, selecting the main news can be carried out using methods such as Group Algorithm Programming Analysis, along with other methods for comparison to achieve optimal results. Decision-making is a crucial stage underlying human activity both individually and collectively. The function of decision-making is futuristic, meaning it relates to the future and has long-lasting effects. Therefore, applications using the Group Algorithm Programming Analysis method can assist in the process of selecting the main news in online media